Integrated network pharmacology and cellular assay for the investigation of an anti-obesity effect of 6-shogaol. (16th April 2022) - Jiao, Wenya; Mi, Si; Sang, Yaxin; Jin, Qiuxia; Chitrakar, Bimal; Wang, Xianghong; Wang, Shuo
Highlights: 6-shogaol has the anti-obesity bioactivity. Network pharmacology and molecular docking would be applied to seek the mechanism of 6-shogaol improving obesity. 6-shogaol inhibited 3T3-L1 cells proliferation and differentiation. 6-shogaol regulated PI3K/Akt signaling pathway. Abstract: This study explored the anti-obesity effect of 6-shogaol and the underlying mechanisms by using Network pharmacology for the prediction and verification of molecular targets and pathways of 6-shogaol against obesity. Furthermore, the results were verified by molecular docking and cell experiments. A total of 86 core targets of 6-shogaol towards obesity were identified. Among them, AKT1 and PIK3CA were confirmed by using the molecular docking. In 3T3-L1 preadipocyte model, 6-shogaol significantly inhibited proliferation and differentiation, reducing the accumulation of lipid droplets. Compared with the control group, the inhibition rates of 6-shogaol on TG and TC were 90.8% and 40.0%, respectively. Additionally, 6-shogaol down-regulated the expression of PPAR-γ and C/EBP-α, while it decreased the phosphorylation of IRS-1, PI3K and AKT. This study, for the first time, confirmed the effect of 6-shogaol on improving obesity through PI3K/AKT pathway. An anti-obesity bioactivity study was further recommended for the development of novel anti-obesity products.